OC-031 A Genome-Wide Association Study Identifies PNPLA3 and SLC38A4 as Risk Loci for Alcoholic Hepatitis. (17th August 2016) - Atkinson, S; Way, M; McQuillin, A; Morgan, MY; Thursz, M; ,
Abstract : Introduction: The clinical spectrum of alcohol-related liver disease varies widely but the majority of patients with evolving disease are asymptomatic. However, a small minority of patients develop severe alcoholic hepatitis (SAH), a clinical syndrome manifest as profound hepatocellular failure, often superimposed on cirrhosis. As only a relative minority of patients develop SAH genetic determination of susceptibility has been proposed. A genome-wide association study (GWAS) approach was used to identify potential risk loci for SAH. Methods: Cases with SAH, of self-reported white British ancestry, were recruited prospectively through the Steroids or Pentoxifylline for Alcoholic Hepatitis trial (n = 860). Ancestry-matched controls with alcohol dependence but without alcohol-related liver injury were recruited from the Centre for Hepatology, Royal Free Hospital, London (n = 1191). A two-stage GWAS was performed. DNA samples from an exploratory cohort (332 cases, 318 controls) were genotyped on Illumina CoreExome BeadChips (Illumina, San Diego, USA) at the Wellcome Trust Sanger Institute, Cambridge, UK. The most significantly associated SNPs were genotyped in DNA samples from an independent replication cohort (528 cases, 873 controls) using KASPar chemistry (LGC Genomics, Hoddesdon, UK). Data were analysed in PLINK1.9. Results: The variant rs738409 in patatin-like phospholipase domain-containing protein 3 ( PNPLA3) was associated at genome-wide significance level (PTHRESHOLD <5x10 −8 ; PEXPLORATORY =1.619x10 −8, OR 2.21 [95% CI 1.68–2.91]). Ten additional, independent loci demonstrated suggestive association (PTHRESHOLD <1.1x10 −5 ). Replication genotyping for the lead markers at each locus demonstrated disease association for rs738409 in PNPLA3 (PREPLICATION = 3.47x10 −8 ; PMETA = 8.62x10 −15 ; OR 1.87) and Solute Carrier Family 38, Member 4 ( SLC38A4) (PREPLICATION = 0.029; PMETA = 4.13x10 −5 ; OR 1.32). Conclusion: This first analysis of data from a GWAS of severe alcoholic hepatitis confirms significant risk association with PNPLA3, consistent with the phenotypic overlap with alcohol-related cirrhosis. It also identified SLC38A4 as a potential, novel risk locus for development of alcoholic hepatitis per se ; this gene is predominantly expressed in the liver and is involved in amino acid transport. Disclosure of Interest: None Declared